Research on infrared emission spectra of pulverized coal ash deposits - Saljnikov Aleksandar (FME Transactions, 2013)
This paper deals with thermal radiation properties of ash deposits on a pulverized coal boiler of an electric power plant. Normal emittance spectra in the 2.5-25 μm interval, and total normal emittance, were measured on 2 kinds of ash layers of a mm magnitude order thickness, at 560→1460→560 K in heating and cooling. The emittance increases with ash radiation wavelength and temperature. Ash powder is sintered and fused above 1200 K. The emittance of the sintered layer is above that of the unsintered layer. The authors propose, and explain by example, correlating the experimentally obtained emittance spectra of ash deposits with a continuous curve, the formula of which defines the dependence of the emittance on wavelength and temperature, i.e. ε = ε (λ,T). Use of this formula, with parameter values determined by the proposed methodology, may greatly simplify the practical application of the experimentally determined emittances in the thermal design of existing and new steam boiler furnaces.